Participant recruitment and retention in randomised controlled trials of melanoma surveillance: A scoping review - Deonna M. Ackermann; Karen Bracken; Jolyn K. Hersch; Monika Janda; Robin M. Turner; Katy J.L. Bell (Contemporary Clinical Trials Communications)
Background: This scoping review aims to collate and describe data on recruitment, retention, and strategies used to improve these, in randomised controlled trials of melanoma surveillance. Methods: We searched MEDLINE, EMBASE, CINAHL and CENTRAL databases from inception until October 23, 2023. Two reviewers screened titles and abstracts, and full-texts, and one reviewer extracted data (convenience sample (n = 5) checked by a second). Eligibility criteria included: (i) RCT design, (ii) clinical setting, (iii) participants at increased risk of melanoma, (iv) interventions for early melanoma detection, and (v) early detection outcomes or surrogates such as improved skin self-examination. We calculated summary statistics and undertook qualitative data synthesis. Results: From 1746 records, 21 trials (reported in 28 papers) were included. Recruitment sources included dermatology clinics, general practice sites, and hospital databases or registries. Trials reported proportions of those screened who were eligible (mean 75 %, range 24–100 %), proportions of those eligible who were randomised (mean 63 %, range 24–95 %), numbers randomised per month (mean 25 participants, range 2–74), and proportion of those randomised who completed outcome measurements (mean 85 %, range 59–100 %) for self-report questionnaires at primary timepoints). Recruitment strategies included targeted participant identification and flexible consent processes. Retention strategies included setting narrow eligibility criteria, reminders, and financial incentives. Reporting on strategies was limited and there were no reports on effectiveness. Few studies reported recruiter facing initiatives or public and patient involvement. Discussion: More consistent and detailed reporting of recruitment and retention strategies in RCTs is needed, alongside evaluations of their effectiveness.